Molecular and Functional Characterization of Trehalase in the Mosquito Anopheles stephensi - Tevatiya, Sanjay; Kumari, Seena; Sharma, Punita; Rani, Jyoti; Chauhan, Charu; Das De, Tanwee; Pandey, Kailash C.; Pande, Veena; Dixit, Rajnikant (Frontiers in Physiology, 2020)
Like other insects, in blood-feeding mosquitoes, trehalase (TRE; EC 3.2.1.28), an enzyme that metabolizes trehalose, may influence a wide array of functions including flight, survival, reproduction, and vectorial capacity, but its role has not been investigated in detail. Here, we characterized a 1839 bp long transcript, encoding 555 aa long trehalase-2 homolog protein from the mosquito Anopheles stephensi. With a conserved insect homology, and in silico predicted membrane-bound protein, we tested whether trehalase (As-TreH) also play a role in mosquito physiologies. Constitutive expression during aquatic development or adult mosquito tissues, and a consistent up-regulation until 42 hrs of starvation, which was restored to basal levels after sugar supply, together indicated that As-TreH may have a key role in stress tolerance. A multifold enrichment in the midgut (p< 0.001819) and salivary glands (p<4.37E-05) of the Plasmodium vivax-infected mosquitoes indicated that As-TreH may favor parasite development and survival in the mosquito host. However, surprisingly, after the blood meal, a consistent up-regulation until 24hr in the fat body, and 48hr in the ovary, prompted to test its possible functional correlation in the reproductive physiology of the adult female mosquitoes. A functional knockdown by dsRNA-mediated silencing confers As-TreH ability to alter reproductive potential, causing a significant loss in the egg numbers (p<0.001), possibly by impairing energy metabolism in the developing oocytes. Conclusively, our data provide initial evidence that As-TreH regulates multiple physiologies and may serve as a suitable target to designing novel strategies for vector control.